Calcula.

a) 6+ [5+(7+2)]

b) 8+ [4-(3+5)]

c) 10- [6+ (2+7)]

d) 15- [2- (6-10)]

e) 15- [10- (8+4)]

f) 12- [7- (2-10)]

g) (-6) + [5+ (2- 12)]

h) (-7) - [3- (4-9)]

i) (2-10) + [5- (8+2)]

j) (12-3) - [1- (2-6)]

k) [9- (+5)] + [7+ (-10)]

l) [10- (-2)] - [5- (+12)]

m) [8- (6+4)] - (5-7)

n)

2

Respuestas

¡La mejor respuesta!
2012-07-09T18:42:35+02:00

a)  6 + [ 5 + (7+2)] = 6 + 5 + 8 = 19

 

b) 8 + [4 - (3+5)] = 8 + 4 -8 = 4

 

c) 10 - [6 + (2+7)] = 10 -[15] = 10 -15 = -5

 

d) 15 - [2 - (6-10)] = 15 - [2 + 4] = 15 - 6 = 9

 

e) 15 - [10 - (8+4)] = 15 - [10 -12] = 15 + 2 = 17

 

f) 12 - [7 - (2-10 )] = 12 - [7 + 8] = 12 - 15 = -3 

 

g) (-6) + [5 + (2-12)] = -6 + 5 -10 = -11 

 

 

h) (-7) - [3 - (4-9)] = -7 -[3 +5] = -7 - 8 = -15 

 

i) (2-10) + [5 - (8 +2)] = -8 + 5 -10 = -13 

 

j) (12-3) - [1 - (2-6)] = 9 - [1 +4] = 9 -5 = 4 

 

k) [9 -5] + [7-10] = 4 -3 = 1

 

l) [10 +2] - [5 -12] = 12 -[-7] = 12 +7 = 19 

 

m) [8 - 10] - (-2) = -2 +2 = 0 

 

n) [1 -3] - (-4) = -1 +4 = 3

 

Elijeme como mejor respuesta 

2012-07-09T20:29:49+02:00

a) 

a) 6+  [5+(9)]= 6+14= 20

b) 8+  [4-(8)]=8+  [-4]= 4

c) 10-  [6+ (9)]= 10 - 15 = -5

d) 15-  [2- (-4)]= 15 -[6]= 9

e) 15-  [10- (12)]= 15- [-2]= 17

f) 12-  [7- (-8)]= 12-  [15]= -3

g) (-6) + [5+ (-10)]= (-6) + [-5]= -11

h) (-7) -  [3- (-5)]= (-7) -  [8]= -15

i) (-8) + [5- (10)]=(-8) + [-5]= -13

j) (12-3) - [1- (2-6)]=(9) - [1- (-4)]=(9) - [5]= 4

k) [9- (+5)] + [7+ (-10)]= [4] + [-3]= 1

l) [10- (-2)] - [5- (+12)]= [12] - [7]= 5

m) [8- (6+4)] - (5-7)= [8- (10)] - (-2)=[-2] - (-2)=0

n) [1+ (6-9)] - (8-12)= [1+ (-3)] - (-4)= [-2 ] - (-4)= 2